Educating Physicians for Rural America: Validating Successes and Identifying Remaining Challenges With the Rural Medical Scholars Program. (20th March 2017) - Wheat, John R.; Leeper, James D.; Murphy, Shannon; Brandon, John E.; Jackson, James R.
Abstract: Purpose: To evaluate the Rural Medical Scholars (RMS) Program's effectiveness to produce rural physicians for Alabama. Methods: A nonrandomized intervention study compared RMS (1997‐2002) with control groups in usual medical education (1991‐2002) at the University of Alabama School of Medicine's main and regional campuses. Participants were RMS and others admitted to regular medical education, and the intervention was the RMS Program. Measures assessed the percentage of graduates practicing in rural areas. Odds ratios compared effectiveness of producing rural Alabama physicians. Findings: The RMS Program (N = 54), regional campuses (N = 182), and main campus (N = 649) produced 48.1% (odds ratio 6.4, P < .001), 23.8% (odds ratio 2.5, P < .001), and 11.2% (odds ratio 1.0) rural physicians, respectively. Conclusions: The RMS Program, contrasted to other local programs of medical education, was effective in producing rural physicians. These results were comparable to benchmark programs in the Northeast and Midwest USA on which the RMS Program was modeled, justifying the assumption that model programs can be replicated in different regions. However, this positive effect was not shared by a disparate rural minority population, suggesting that models for rural medical education must be adjusted to meet the challenge of such communities for physicians.